2009
DOI: 10.1063/1.3118681
|View full text |Cite
|
Sign up to set email alerts
|

Formation of lamellar structures from spherical particles

Abstract: We report disorder to lamellar transition in a system of spherically symmetric particles where the interparticle potential consists of a short-ranged attraction and a longer-ranged repulsion. The system provides a simplified model for aqueous dispersions of colloidal particles and globular proteins that may exhibit stable/metastable clusters or microscopic phases. By using a non-mean-field density functional theory, we predict that under appropriate conditions, a lamellar phase with alternating condensed and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Toward this end, remarkable advances have been achieved on the basis of statistical mechanics for example, density functional theory (DFT) and integral equation theory. In particular, DFT turns out to be robust in the study of inhomogeneous fluids. In the past a few decades, a large number of various versions of DFT have been proposed. …”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, remarkable advances have been achieved on the basis of statistical mechanics for example, density functional theory (DFT) and integral equation theory. In particular, DFT turns out to be robust in the study of inhomogeneous fluids. In the past a few decades, a large number of various versions of DFT have been proposed. …”
Section: Introductionmentioning
confidence: 99%
“…The model given by Equation (2) in dimension d ¼ 2 was studied by Imperio and Reatto [4][5][6]. A slightly modified version of this model in d ¼ 3, where the exponential functions were replaced by Yukawa interactions, was studied Reatto and colleagues [8][9][10] and also inspired studies by Archer et al [11,12] and by Li et al [13].…”
Section: Introductionmentioning
confidence: 96%
“…A few studies regarding the influence of confinement on the phase behavior of a competing system has been reported in the slit-type pore. 9,11,[13][14][15] More recently, Kim et al 15 had shown that the periodic spacing of the modulated structure is commensurate with the periodicity of modulation in the particle density distribution and the cluster phase only appears when the periodic spacing is greater than the slit width. Here, one of the important questions we consider is how the geometry of the pores, the size of the pores, and the competing interaction affect the structure and phase behaviors of a confined competing system.…”
Section: Introductionmentioning
confidence: 98%
“…The competing system is an interesting model, which has an attractive interaction at a short distance and a repulsive one at a long distance. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Such a competing system gives rise to various microphase separated phases including the cluster phases. Many studies have been made to understand microphase formations induced by the competing interactions in the bulk and confined phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation